A process model for underground coal gasification – Part-I: Cavity growth. (1st October 2016) - Samdani, Ganesh; Aghalayam, Preeti; Ganesh, Anuradda; Sapru, R.K.; Lohar, B.L.; Mahajani, Sanjay
Highlights: UCG process is divided in two phases based on growth pattern of the cavity. Proposed a compartment model for phase-I based on virtual RTD studies using CFD. Integrated non-ideal flow patterns with spalling and detailed kinetics of the given coal. Model predictions are in agreement with the results of lab-scale UCG experiments. Abstract: In underground coal gasification (UCG), a cavity is formed in the coal seam due to consumption of coal. The irregular-shaped cavity consists of a spalled-rubble on the cavity floor, a cavity roof and a void zone between the two. Depending on the cavity growth pattern, UCG process can be divided into two distinct phases. In phase-I, coal/char near injection well gets consumed and cavity grows in a vertical direction and hits the overburden. Phase-II starts thereafter, in which the cavity grows in the horizontal direction toward the production well. This paper presents an unsteady-state model for gas production during phase-I for a coal under consideration for UCG. The non-ideal flow patterns in the cavity are determined using computational fluid dynamics (CFD). The CFD results and residence time distribution (RTD) studies show that the complex UCG cavity can be reduced to a computationally less time consuming compartment model consisting of a radial plug flow reactor (PFR) followed by a continuous stirred tank reactor (CSTR). The developed compartment model incorporates reaction kinetics, heat-transfer, mass-transfer, diffusional limitations and thermo-mechanical failure effects for the coal of interest. The model is tested on a lab scale UCG; it can predict the location of reaction and drying fronts, profiles of solid and gas compositions, exit gas calorific value and cavity growth rates. Further, the model predictions show an excellent match with the cavity growth rate and exit gas quality observed during laboratory-scale UCG-like experiments on the coal of interest. Therefore, the model can potentially be used to determine feasibility of UCG for any other coal for the known kinetics and spalling parameters.